2013
DOI: 10.1093/ajh/hps039
|View full text |Cite
|
Sign up to set email alerts
|

Increased Aortic Pulse Wave Velocity Is Associated With the Presence of Angiographic Coronary Artery Disease in Overweight and Obese Patients

Abstract: Arterial stiffness indices were not consistently associated with obesity, opposite to what might have been expected. The association of increased CFPWV with the presence of angiographic CAD in patients with increased BMI or WC values warrants further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
4
18
0
4
Order By: Relevance
“…However, this association is likely diseasestage specific, as it was shown to be particularly strong in adult patients with angiographic evidence of changes in coronary arteries. 22 In our study, children with obesity and arterial hypertension presented with significantly higher values of PWV when compared to both controls and obese normotensive subjects. There were no statistically significant differences in PWV between obese normotensives and controls.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…However, this association is likely diseasestage specific, as it was shown to be particularly strong in adult patients with angiographic evidence of changes in coronary arteries. 22 In our study, children with obesity and arterial hypertension presented with significantly higher values of PWV when compared to both controls and obese normotensive subjects. There were no statistically significant differences in PWV between obese normotensives and controls.…”
Section: Discussionsupporting
confidence: 49%
“…5 This parameter turned out to be correlated with the presence of obesity and coronary artery disease in adults. 22 In the case of children and adolescents, this association was more evident in patients with arterial hypertension than in obese individuals. 7,9 However, we did not find a similar relationship in our material; the only predictors of Aix@75, both in the whole group of children and in their subsets with/without overweight/obesity and arterial hypertension, were age, sex, HR, LV mass, LAD and cDia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main determinants of PWVcf were age and systolic blood pressure, 29 while AIx was associated with systolic blood pressure 30,31 and female gender, 32 and inversely with height 33 and central obesity probably due to decreased peripheral wave reflections. 15 PWVcr was mainly determined by diastolic blood pressure and gender as discussed above; these associations have not been previously reported. 34 In the current study, SI was found to be associated with peripheral arterial stiffness of the upper limb (PWVcr), while there was a trend for a significant association with AIx.…”
Section: Discussionmentioning
confidence: 79%
“…Importantly, increased central vascular pulse wave velocity (PWV), a measure of arterial stiffening, is independently associated with CVD event risk (31). Accelerated arterial stiffening occurs in obesity whereby increased body mass index is associated with reduced arterial distensibility as early as adolescence (39,49,51) and is associated with angiographic evidence of coronary artery disease later in life (3). Thus, arterial stiffening is a significant contributor to and predictor of CVD development and progression.…”
Section: Associated With Endothelial Dysfunction Aberrant Extracellumentioning
confidence: 99%